The role of social capital and social media in tourism development towards the wellbeing of the Mah Meri community in Carey Island, Malaysia - Abd Hamid, Zuliah; Kunasekaran, Puvaneswaran; Alam, Mehtab (Universiti Putra Malaysia, 2025)
The study aims to close the social media and social capital gaps for sustainable indigenous tourism. It encompasses social media’s active participation, social capital, and community sources for sustainable indigenous tourism on Carey Island, Malaysia’s Mah Meri. The utilisation of social media in the development of Indigenous tourism is shaped by the application of social capital theory and a quantitative methodology. The application of social media to sustainable tourism fills the gap in the Social Capital Theory. Structural equation modelling (SEM) and partial least squares (PLS) analysis aim to assess the relationship between exogenous and endogenous factors. The outcomes revealed that community sources (including culture, nature, and knowledge) and social media (adaption, participation, interactivity and sharing) significantly influenced sustainable Indigenous tourism. The results of a hierarchical multiple regression analysis used to moderate factors showed that income and educational attainment significantly influenced the association between social capital and sustainable Indigenous tourism. The results of this study contributed fresh insights into the literature on tourism that leverages community social capital.